Strategi pengembangan produk baru dan siklus hidup produk: studi kasus nokia - Ariwibowo, Yusuf Ageng; Rahayu, Yayuk; Khasanah, April; Faizah, Nilna (Maliki Interdisciplinary Journal, 2025)
The development of new products and the management of the Product Life Cycle (PLC) are essential aspects in maintaning a company’s competitiveness in a dynamic industry. This article discusses how product innovation strategies can be applied across various stages of the PLC, from introduction to decline, using nokia as a case study. Through this analysis, it is evident that continous innovation and adaptive marketing strategies are key factors in extending the product’s lifecycle. Futhermore, the discussion highlights the importance of collaboration between product development and marketing in navigating the ever-changing market dynamics. The company’s internal capabilities, such as finance and human resources, must also be considered. With careful planning and a systematic approach, companies can create successful products, meet consumer needs, and drive sustainable business growth. Only by understanding and adapting to market changes can companies maintain their competitiveness.